PHOTOELECTROCHEMICAL SOLAR CELLS BASED ON DYE-SENSITIZATION OF NANOCRYSTALLINE TIO2 - Gebeyehu, Desta; Sariciftci, N. Serdar (Zede Journal of Ethiopian Engineers and Architects, 2023)
Dye-sensitized solar cells (DSCs) have attracted considerable interest as low-cost alternatives to conventional inorganic photovoltaic devices. With low-cost raw materials and relatively low-cost manufacturing technology and processes, deposited thin films have the potential to provide more than a 50 percent reduction in cost relative to traditional crystalline cell modules. Hence, we investigated the photoelectrochemical properties of mesoporous colloidal anatase films in connection ·ith their potential application in liquid junction photovoltaic cells. A respectable light to electric energy conversion efficiency of about 9.5% in 9 mW/cm2 (- 1110 Sun) was obtained. Jn comparison (a lsc = 2.2 mA/cm1 and an V0c = 600 mV under a white light l7lumination of 9 m W!cm1 ), we obtained !Jc = 15 mA!cm’ and V oc 7 60 m Vat a light intensity of 85 mW/cm1 (direct Sun). We achieved extraordinary efficiency for the conversion of incident photons to converted electrons exceeding 80% within the wavelength range of the absorption band from RuL2(NCS)2: 2 TBA sensliizer.